Quality of life among adolescents aged 14 to 18 years with Beta-Thalassemia Major (TM) in Qatar - Nashwan, Abdulqadir J; Yassin, Mohamed A; Babu, Ganga Devi J; Nair, Sindhumole L K; Libo-on, Izette L; Hijazi, Hothaifah A; de Sanctis, Vincenzo; Soliman, Ashraf (Acta Biomedica Atenei Parmensis, 2018)
Background: Thalassemia  is a heterogeneous group of inherited disorders of hemoglobin synthesis. It is a common disease in Mediterranean, Southeast Asia, Indian subcontinent, and Middle East countries, including Qatar. Purpose: The aim of this study was to assess the quality of life (QOL) among patients aged 14 to 18 years with thalassemia major (TM) in Qatar and correlates their QOL with bio-demographic data of the patients compared to healthy controls. Materials and Methods: This cross-sectional study measured the QOL in adolescents with thalassemia major who were attending ambulatory units in a tertiary hospital in Qatar. Forty children and adolescents with TM and 40 healthy participants were enrolled in the study. Forty-two (52.5%) participants were males and 38 (47.5%) females. Data were collected utilizing PedsQLTM 4.0 generic core scale and were analyzed using the appropriate statistical method. Results: Children with TM had significantly lower and more variable overall quality of life score (69.1 ± 16.8) compared to healthy matched children (77 ± 12.8), (p